Reflections of South Africa Student Leaders 1994-2017 - Luescher, Thierry M. (African Minds, 2020)
Reflections of South African Student Leaders 1994-2017 brings together the reflections of twelve former SRC leaders from across the landscape of South African universities. Each student leader's reflections are presented in a dedicated chapter that draws closely on an interview conducted in the course of 2018/19 which was followed by an interactive process of co-editing, correcting, and approving the chapter between the researchers and the student leaders.